Pengaruh Kualitas Pelayanan Karyawan terhadap Kepuasan Konsumen - Hayatul Millah (Fakultas Ekonomi dan Bisnis Islam, 2020)
This study aims to determine the effect of employee service quality on consumer satisfaction Alfamart Karangbong Village, Pajarakan District. This type of research is quantitative descriptive research, quantitative descriptive research is a method that explains or analyzes a problem from a data based on the calculation of numbers with statistical analysis of research results. The data analysis method used in this study is a simple linear regression analysis. The quality of employee services has a positive and significant effect on customer satisfaction with Alfamart Karangbong Pajarakan.